O processo de implementação da educação do campo nas escolas do Núcleo Regional de Educação de Pato Branco: limites, desafios e possibilidades - Outeiro, Marlete Turmina (2015)
This work is part of the Graduate Program in Regional Development of the Federal Technological University of Paraná, Pato Branco campus, the research line Education and Development. The line of research concerns the Regionality and Development. In this study, investigate sought the implementation of the Field Education Curriculum Guidelines in the State of Paraná, whose locus, SEED / PR, the NRE / Pato Branco and Field Schools belonging to the NRE. The theme is to respond to the research problem, to identify the limits and challenges of the implementation process of Rural Education in rural schools in the Regional Center of Pato Branco Education. Exploratory research covers a time frame comprising the years 2002-2014 in order to identify and analyze the documents and perceptions of the subjects that guide the implementation of the field of education in the state of Paraná. The results show that the education field has not yet overcame the challenge of implementing public policies, in particular the field of Education Curriculum Guidelines. In general, the texts point to the concerned school education with the urban environment, in an attempt to solve the problems related to truancy, low school enrollment,flunk, among others. The reality of the field displays more serious such problems, however, is visible the development of proposals in an attempt to achieve definitive solutions to the issues of the field. However, a positive factor is the increase in continuing education courses, some offered by the Department of Education Field Regional Center of Education, others initiatives by the own teacher, which demonstrate the concern in improving their teaching practices, concomitant with need to change the identity of the field school. In this sense, we seek to deepen the discussion in order to demystify the idea that the subject field to be synonymous with poor education, poor quality. Documents such as the Field Operational Guidelines established by the CNE - National Education Council in 2002, the Curriculum Guidelines field developed by SEED - Secretary of State and Education in the State of Paraná in 2004 and established as a public policy in 2010 provide data that allow make a study of public policy and educational field context in order to understand the challenges for the development of an education as culture, ways of life, history, finally, the specificities of the subject field.